Bullying in North American Schools. - Espelage, Dorothy L.; Swearer, Susan M. (Taylor & Francis, 2010)
Forty-three states have now passed statutes mandating that schools have a bullying policy in place, a remarkable increase since the first edition of Bullying in American Schools was published in 2004. Although these statutes vary in their requirements, most school districts realize that bullying behavior has to be addressed through through targeted prevention and intervention efforts. This book provides an exciting compilation of research on bullying in school-aged youth by a representative group of researchers, including developmental, social, counseling, school, and clinical psychologists across North America. Its social-ecological perspective illustrates the complexity of bullying behaviors and offers suggestions for databased decision-making to intervene and work to reduce bullying behaviors. The book provides empirical guidance for school personnel as they develop bullying prevention and intervention programs or evaluate existing programs. Key features Ecological Perspective - The book is organized by a social-ecological perspective in which bullying is examined across multiple contexts including individual characteristics, peer and family influences, and classroom dynamics. An introductory chapter explains the tenets of the social-ecological framework and how each chapter exemplifies this perspective. Empirical Research - Chapters include basic research data on bullying and victimization from samples in the United States and Canada. Evaluation data for existing programs are also presented. Implications for Practice - Service providers (teachers, school psychologists, counselors, school administrators, school social workers, psychotherapists in private practice) will learn the practical implications of various types of programs and how to choose and implement one that fits their school ecology. Expertise - Chapter authors, all of whom are leaders in the area of bullying research in the United States and Canada, were selected on the basis of the following criteria: 1) they have an active bullying research program within North American schools 2) their theoretical framework is social-ecological and 3) their findings have practical implications for school service providers as well as for future research.